Personal identity as a problem of modern society - Pischikov, Volodymyr; Kholin, Mykhailo (Actual Problems of Mind, 2017)
The crisis of personal identity is only one of the manifestations of the cultural crisis of modern society. The foundations of a bourgeois technogenic civilization must be radically transformed.